Optimization of the optoelectronic properties of copper zinc tin sulfide thin films for solar photovoltaic applications. (12th October 2021) - Gunavathy, K V; Arulanantham, A M S; Khan, Aslam; Raj, C S A; El-Toni, Ahmed M; Shar, Muhammad A; Ansari, Anees A; AlFaify, S
Abstract: Copper Zinc Tin Sulfide (CZTS), a successful contender for environmentallybenign thin film photovoltaics was successfully prepared on soda-lime glass substrates through an economically feasible nebulizer assisted spray pyrolysis technique. Further, a solar cell structure withn-CdS/p-CZTSheterojunction was fabricated to study the performance of the nebulizer sprayed CZTS absorber layer using different precursor solutions for copper such as copper acetate, copper chloride, and copper nitrate. Investigations were done to ascertain the influence of different copper precursors on the optoelectronic properties of CZTS thin films by systematically analyzing their characteristics determined by using different analytical techniques. X-ray diffraction studies show a preferential orientation along (112) plane for the deposited kesterite film. The obtained film thickness and crystallite size were found to be 507 nm and 8 nm, respectively, for the film derived from copper nitrate based spray solution. AFM morphological analysis also confirmed a higher particle size for copper nitrate based CZTS film whose band gap was found to be 1.50 eV. The absorption characteristic was also in the favor of nitrate form of the copper precursor which shows a higher absorption value in the visible region than the rest of the samples. Its carrier concentration was found to be 8.06 × 10 17 cm −3 which is 4 times higher than the rest of the films and mobility was found to be of the order of 12.3 cm 2 V −1 s −1 . The open circuit voltage, short circuit current, fill factor, and efficiency of copper nitrate based CZTS solar cell structure was found to be better and is determined to be 0.27 V, 2.51 mA cm −2, 24.3%, and 0.165%.